Development of freeze-dried lactic acid bacteria starter for coffee fermentation: Optimizing incubation time and coating formulation - Tawali, Abu Bakar; Amelia, Vemy; Zainuddin, Zaraswati Dwyana; Zainal, Zainal; Nur, Nadiah; Mahendradatta, Meta; Fitri, Fitri; Ramli, Andi Rahmayanti (jurnal1, 2025)
This study aimed to develop a freeze-dried lactic acid bacteria (LAB) starter for coffee fermentation by optimizing incubation time and coating formulation. The research was conducted in two stages: determining the optimal incubation time for the liquid coffee starter and formulating the dry starter coating material. The liquid starter was prepared using coffee skin powder, glucose, peptone, and minerals, and inoculated with Lactobacillus plantarum, Weissella sp., and Leuconostoc mesenteroides. Incubation was performed at room temperature for 24, 28, 32, and 36 h. The optimal incubation time was found to be 32 h, resulting in a LAB viability of 4.2x1013 CFU/mL and a total acid content of 1.76%. The dry starter was prepared by encapsulating the liquid starter with various coating materials (gelatin and gum arabic) at different concentrations (5, 6, and 7%) using the freeze-drying method. The formulation with 5% gum arabic best maintained cell viability at 46.77% over a 4-week storage period. Coffee fermentation using the dry starter showed improved organoleptic qualities, with the best results obtained after 48 h of fermentation. This study presents a sustainable approach to producing high-quality fermented coffee, such as Luwak coffee, without the use of animals.